2015
DOI: 10.1002/cbin.10427
|View full text |Cite
|
Sign up to set email alerts
|

Fndc5 overexpression facilitated neural differentiation of mouse embryonic stem cells

Abstract: Fndc5 has been recently recognized as a myokine which could be cleaved and secreted into blood stream. It is termed as irisin with an important role in thermogenesis and energy homeostasis. Increased expression of Fndc5 has been reported upon retinoic acid treatment during neural differentiation and its knockdown decreased neural differentiation and neurite outgrowth. This study tries to evaluate the effect of Fndc5 overexpression on rate of neural differentiation in mouse. (Thus, transduced cell line of mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…On the other hand, forced expression of FNDC5 during neuronal precursor formation from mouse embryonic stem cells increased mature neuronal markers (Map2, b-tubulinIII and Neurocan) and astrocyte marker (GFAP) and BDNF. However, overexpression of FNDC5 in undifferentiated mouse embryonic stem cells did not have these effects, indicating that FNDC5 supports neural differentiation rather than lineage commitment (Forouzanfar et al, 2015). Pharmacological doses of recombinant irisin increased cell proliferation in the mouse H19-7 hippocampal cell line (Moon et al, 2013).…”
Section: Fndc5/irisin In Neuronal Developmentmentioning
confidence: 99%
“…On the other hand, forced expression of FNDC5 during neuronal precursor formation from mouse embryonic stem cells increased mature neuronal markers (Map2, b-tubulinIII and Neurocan) and astrocyte marker (GFAP) and BDNF. However, overexpression of FNDC5 in undifferentiated mouse embryonic stem cells did not have these effects, indicating that FNDC5 supports neural differentiation rather than lineage commitment (Forouzanfar et al, 2015). Pharmacological doses of recombinant irisin increased cell proliferation in the mouse H19-7 hippocampal cell line (Moon et al, 2013).…”
Section: Fndc5/irisin In Neuronal Developmentmentioning
confidence: 99%
“…numerous genes serve an important role in the differentiation into neural stem cells (52,53). a recent study demonstrated that fibronectin type III domain-containing 5 facilitated neural differentiation by increasing the expression of brain derived neurotrophic factor (54). Zfhx1b gene expression has been confirmed to be notably upregulated via the fibroblast growth factor signaling pathway in meScs cultured in a permissive neural-inducing environment (19).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, overexpression of Fndc5 significantly increases neural differentiation precursor markers and mature neuron markers. All these data suggest that FNDC5 may facilitate neural differentiation (21). Further studies (22) indicate that FNDC5 stimulates neural differentiation via the extracellular-signal-regulated kinase 1/2(ERK1/2) signaling pathway.…”
Section: Effects Of Irisin On Neural Differentiationmentioning
confidence: 96%